An intrachromosomal insertion causing 5q22 deletion and familial adenomatous polyposis coli in two generations. Issue 3 (March 1992) - Cross, I; Delhanty, J; Chapman, P; Bowles, L V; Griffin, D; Wolstenholme, J; Bradburn, M; Brown, J; Wood, C; Gunn, A
Abstract : We report familial adenomatous polyposis coli (FAPC) with epidermoid cysts, osteomata, and areas of congenital hypertrophy of the retinal pigment epithelium (CHRPEs) in a male patient and his maternal aunt, both of whom suffered a mild to moderate degree of mental handicap. Both had an interstitial deletion of the long arm of chromosome 5 (del(5)(q22q23.2)). Two other normal family members had the underlying direct insertion of chromosome 5(dir ins(5)(q31.3q22q23.2)). Molecular genetic and fluorescent hybridisation studies have shown that loci D5S37 and D5S98 are outside the deletion whereas loci detected by probes EF5.44 and YN5.48 are lost. As expected, the molecular analyses indicate loss of one allele at the MCC and APC loci. The APC gene is located within band 5q22. Familial direct insertions should be considered as a cause of recurrent microdeletion syndromes.